Forensic Assistance Project: Consultant Report 1999-008 Draganovac-Jezero I Federation Commission on Missing Persons - Bosniak Side - Physicians for Human Rights
Forensic report on individual and mass grave exhumations in Bosnia and Hercegovina created during the Forensic Assistance Project (FAP). The report was authored by: Drayer, Francine On 28 April 1999, the Federation Commission on Missing Persons - Bosniak Side, exhumed human remains from two locations in the vicinity of Jezero (Jajce). The team recovered the remains of 23 individuals (ten women, nine men and four children) from a mass grave near Draganovac. The remains of a single individual were recovered from Gorni Mujdžići. The 23 victims recovered from the site at Draganovac were reported to have been amongst 28 civilians rounded up in September of 1992. 5 managed to escape while the remaining 23 were shot and buried. Place of Exhumation: Draganovac-Jezero Exhumation Site: Draganovac, Gornji Mujdžići, Natpolje Date of Exhumation: 28 April 1999 Minimum Number of Exhumed Individuals: 024